The maternal periodontal disease as a risk factor of intrauterine growth retardation - Carranza Samanez, Maynor (2010)
This study evaluates the relationship between the intrauterine growth retardation (IUGR) and the maternal periodontal disease (MPD). This case-control study of 120 mothers, 38 cases (mothers of babies with IUGR) and 82 controls (mothers of babies without IUGR) at the “Madre Niño San Bartolomé” Teaching Hospital. The mothers were interrogated and their medical histories were reviewed. Data was recorded, such as: the education level, marital status, smoking, alcohol and drug habits. All the mothers were examined within two days after the delivery. Only one examiner evaluated the plaque, gingival and periodontal components through the modified periodontal disease index (PDI) that observes the probing depth, clinical attachment level, proving bleeding, gingival inflammation and plaque presence. The frequency distribution and the Odds Ratio test were calculated. We found out that the maternal periodontal disease increases a little the probability of having children with IUGR [plaque conditions OR 1.49 (IC 95% 0.13-1.96), gingival conditions OR 1.36 (95% IC 1.06-1.74) and periodontal conditions OR 1.32 (IC 95% 0.09-1.82)]. It can be concluded that the maternal periodontal disease does not represent a substantial risk factor for intrauterine growth retardation.